2006
DOI: 10.1007/bf03327435
|View full text |Cite
|
Sign up to set email alerts
|

Stress and dementia: the role of the hypothalamic-pituitary-adrenal axis

Abstract: Hippocampus plays a crucial role in learning and memory and, in spite of its remarkable plasticity, it is also particularly sensitive to stress hormones due to its high concentration of corticosteroid receptors. Indeed, adrenal steroids modulate hippocampal plasticity, acting on excitability and long term potentiation or depression. By a chronobiological approach, we studied the cortisol and DHEAS secretion in clinically healthy old subjects and in age-matched demented patients, including both the degenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 14 publications
0
68
0
4
Order By: Relevance
“…It has also been shown that chronic life stress among healthy women prospectively predicts reductions in gray matter volume in the hippocampus (Gianaros et al 2007) and cortisol levels correlate with hippocampal volume (Lupien et al 1998). Chronic stress has thus been hypothesized to play a crucial role in development of dementia (Magri et al 2006). Gallo and Matthews hypothesize that SEP effects on health are partially mediated by the influence of negative emotions such as hostility, hopelessness, depression or anxiety (Gallo and Matthews 2003).…”
Section: Psychological/psychosocial Stressorsmentioning
confidence: 96%
“…It has also been shown that chronic life stress among healthy women prospectively predicts reductions in gray matter volume in the hippocampus (Gianaros et al 2007) and cortisol levels correlate with hippocampal volume (Lupien et al 1998). Chronic stress has thus been hypothesized to play a crucial role in development of dementia (Magri et al 2006). Gallo and Matthews hypothesize that SEP effects on health are partially mediated by the influence of negative emotions such as hostility, hopelessness, depression or anxiety (Gallo and Matthews 2003).…”
Section: Psychological/psychosocial Stressorsmentioning
confidence: 96%
“…This leads to a down-regulation of precursor cell proliferation in the adult dentate gyrus (Gould et al 1997;. The stress-induced effects of glucocorticoids have been linked to age-related cognitive problems in humans (Heffelfinger and Newcomer 2001;Magri et al 2006). In animal models, the effects of chronic stress and chronically high levels of corticosterone on adult neurogenesis have been rather difficult to assess, and the data do not yet provide a clear picture.…”
Section: Mechanisms Of Activity-dependent Regulationmentioning
confidence: 99%
“…It also plays a key role in the endocrine functions of the hypothalamic-pituitary-adrenal axis (Miller and O¢Callaghan 2005;Magri et al 2006). As it is a principal neural target tissue for GCs, it is, therefore, reasonable to assume that such action may lead to specific cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%